2020
DOI: 10.3390/foods9070939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Different Aloe vera Gel-Based Edible Coatings on the Quality of Fresh-Cut “Hayward” Kiwifruits

Abstract: In recent years, the market for minimally processed fruit has increased. Fresh-cut fruits are characterized by a short shelf life due to the processing phases that accelerate the ripening courses. The aim of this work is to analyze the effect on the quality of fresh-cut Hayward kiwis of three different edible coatings based on (1) Aloe vera gel, (2) Aloe vera gel + hydroxypropyl methylcellulose and (3) Aloe vera gel + lemon essential oil. Fruit firmness, weight loss, color, soluble solids content, titratable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 71 publications
4
31
1
Order By: Relevance
“…Our analysis revealed that TPC varied between 28.50 ± 1.92 (Fino de Jete) and 174.90 ± 11.69 (Chaffey) mg GAE per 100 g of PW, recording an average value equal to 75.18 ± 57.94 mg GAE per 100 g PW. The mean value is higher than those reported for the flesh of other tropical fruits with high commercial impact, including kiwi, papaya, mango and avocado [7,10,45,58]. Furthermore, the mean value for TPC in our fruits was 10-fold higher than for cherimoya fruits from Portugal [59], but 3-fold lower than those obtained for the flesh of fruits from Ecuador [60].…”
Section: Total Phenolic Contentcontrasting
confidence: 81%
See 1 more Smart Citation
“…Our analysis revealed that TPC varied between 28.50 ± 1.92 (Fino de Jete) and 174.90 ± 11.69 (Chaffey) mg GAE per 100 g of PW, recording an average value equal to 75.18 ± 57.94 mg GAE per 100 g PW. The mean value is higher than those reported for the flesh of other tropical fruits with high commercial impact, including kiwi, papaya, mango and avocado [7,10,45,58]. Furthermore, the mean value for TPC in our fruits was 10-fold higher than for cherimoya fruits from Portugal [59], but 3-fold lower than those obtained for the flesh of fruits from Ecuador [60].…”
Section: Total Phenolic Contentcontrasting
confidence: 81%
“…Our results, in agreement with other literature data, demonstrated that cherimoya is a tropical fruit with high nutritional value. Indeed, it had low fat content, while containing an amount of sugars and proteins generally higher than other common tropical fruits, including mango [ 7 ], kiwi [ 45 ], pineapple [ 46 ], and papaya [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aloe vera gel with lemon essential oil and a variant with gelling agent had a positive effect on quality parameters (firmness, color, weight). These variants also reduced the multiplication of microbes level due to gas exchange capability of the natural coating as well as the antimicrobial properties of the essential oils and Aloe vera mucilage [215].…”
Section: Aloe Veramentioning
confidence: 99%
“…In CTR packages, O 2 concentration shrinks consistently compared to MAPN 2 and MAPAr samples after T 4 . The level of O 2 reached by CTR is detrimental, because it promotes anaerobic fermentative reactions leading to unpleasant odors and off-flavors [ 44 ]. O 2 concentration decreases in both MAP treatments with a smaller rate, suggesting a slower respiration rate from the arils inside the bags.…”
Section: Resultsmentioning
confidence: 99%
“…Microbiological analysis was conducted following the work of Passafiume et al [ 44 ]. Different microbial groups were investigated as follows: total mesophilic microorganisms (TMM) on plate count agar (PCA), total psychrotrophic microorganisms (TPM), and yeasts and molds on yeast extract peptone dextrose (YPD) agar supplemented with 0.1-g/L chloramphenicol to avoid bacterial growth.…”
Section: Methodsmentioning
confidence: 99%